Plasma Homocysteine, Serum Folic Acid, Serum Vitamin B12, Serum Vitamin B6, MTHFR, and Risk of Normal-Tension Glaucoma. Issue 2 (February 2016) - Li, Jinmiao; Xu, Fan; Zeng, Rui; Gong, Haijun; Lan, Yuqing
Abstract : Background: This meta-analysis aims to comprehensively evaluate the association between total homocysteine (tHcy) levels, serum folic acid, vitamin B12, vitamin B6 levels, methylenetetrahydrofolate reductase (MTHFR) C677T genotype, and risk of normal-tension glaucoma (NTG). Materials and Methods: A systematic search of the EMBASE and PubMed databases was performed to evaluate plasma tHcy levels, serum folic acid, B vitamins' mean difference, and odds ratios of MTHFR C677T genotype between cases and controls. Results: A total of 7 studies including 458 cases and 555 controls meeting the inclusion criteria were involved in this meta-analysis. There were 4 studies for tHcy (149 cases and 148 controls), 2 studies for vitamin B6, vitamin B12, and folate (90 cases and 82 controls), and 4 studies for MTHFR (343 cases and 449 controls). Overall, the mean plasma tHcy levels, serum folic acids, vitamin B12, and vitamin B6 levels were 1.16 μmol/L [95% confidence interval (CI), −0.13, 2.45], −0.62 μmol/L (95% CI, −1.98, 0.74), 5.81 μmol/L (95% CI, −3.53, 15.14), and −16.79 μmol/L (95% CI, −86.09, 52.51). MTHFR TT genotype was found to be unrelated to NTG risk (odds ratio=1.08; 95% CI, 0.69, 1.69). Conclusion: NTG is not associated with elevated plasma tHcy, serum folic acid, serum vitamin B12, serum vitamin B6, and MTHFR C677T genotype.